ROBUST IMPEDANCE ADAPTIVE CONTROL FOR CONSTRAINED MOTIONS - Indrawanto, Indrawanto; Swevers, J; Brussel, H. Van (Mesin, 2002)
This paper presents a robust adaptive impedance control for robot manipulators. The robust adaptive impedance control is designed to obtain fast and accurate force tracking. The proposed controller does not require special knowledge of robot dynamics and environment models. Lyapunov-based Model Reference Adaptive Control is used to establish a global stability of the tracking errors. Experimental results on an industrial robot are presented to verify the force tracking performance of the proposed controller.